Characterization of Phenolic Compounds and Antiproliferative Effects of Salvia pomifera and Salvia fruticosa Extracts - Koutsoulas, Antonios; Čarnecká, Martina; Slanina, Jiří; Tóth, Jaroslav; Slaninová, Iva (Molecules (Basel, Switzerland), 2019)
The phenolic compounds of methanolic extracts of Salvia pomifera and Salvia fruticosa were identified by liquid chromatography tandem mass spectrometry. Carnosic acid and its metabolite carnosol were the most abundant terpene phenolic compounds of S. fruticosa, while they were completely absent in S. pomifera. The main terpene phenolic constituent of S. pomifera was 12-O-methylcarnosic acid and its mass/mass fragmentation pathway was explained. The detailed mechanism of carnosic acid oxidation to carnosol was suggested. The effects of Salvia extracts and/or carnosic acid, the main diterpene phenolic component of S. fruticosa, on the proliferation and cell cycle of two melanoma cell lines (A375, Mel JuSo) and human fibroblast cell line (HFF) were investigated by MTT assay, PI-exclusion assay and flow cytometry cell cycle analysis. Extract of S. fruticosa more efficiently than S. pomifera extract reduced the proliferation of the human melanoma cells. Carnosic acid showed the most significant effect. The first evidence that carnosic acid affects microtubule dynamics and arrests the cell cycle in the G2/M phase was provided. Collectively, our results demonstrate that these two Salvia species are plants of medicinal interest with perspective for further investigation. Carnosic acid could be the compound responsible for the biological activities of S. fruticosa extracts.
Keywords: LC-MS; cancer; Salvia; Cell Line; epitelové buňky; nádorové buněčné linie; Phenols; 12-O-methylcarnosic acid; carnosic acid; microtubules; Salvia fruticosa; melanoma; diterpeny abietanové; Methanol; Epithelial Cells; cell cycle; Cell Proliferation; Cell Line, Tumor; rostlinné extrakty; Salvia pomifera; Oxidation-Reduction; Antineoplastic Agents; fenoly; cytotoxicity; kontrolní body fáze G2 buněčného cyklu; protinádorové látky; Humans; rozpouštědla; inhibiční koncentrace 50; G2 Phase Cell Cycle Checkpoints; methanol; viabilita buněk; Cell Survival; Fibroblasts; nadzemní části rostlin; Abietanes; proliferace buněk; Inhibitory Concentration 50; Plant Components, Aerial; šalvěj; oxidace-redukce; buněčné linie; Plant Extracts; Solvents; lidé; fibroblasty